The The Relationship between the Media Agenda and the Public Agenda on the Electability of Presidential Candidates - Gama, Betty; Kusharsanto, Adhika Prasetya; Kusumawati, Henny Sri; Widodo, Yoto (Communicology: Jurnal Ilmu Komunikasi, 2024)
Facing the 2024 election, two big figures have emerged who have been nominated as Indonesian presidential candidates for the 202-2029 period, namely Anies Bawesdan from the Nasdem Party and Ganjar Pranowo from PDIP. These two figures then became targets of the media by sharing information and activities carried out. Every report in the mass media is essentially a construction of events by the mass media based on the reality that occurred. The ability to construct this discourse will have a major influence on the opinions, decision making and political attitudes of readers. By understanding the work of media reality construction, people will be wise and appropriate in utilizing any information from the mass media. Solopos.com's media agenda setting regarding the two presidential candidates Anies Bawesdan and Ganjar Pranowo certainly greatly influences the level of electability of readers, especially among FISH Univet Bantara students who were respondents to this research. This research aims to determine the influence of the Solopos.com media agenda setting on the electability level of students in the candidacy of Anies Bawesdan and Ganjar Pranowo in the 2024 election and to analyze the influence of the public agenda on the electability level of students in the candidacy of Anies Bawesdan and Ganjar Pranowo in the 2024 election. The method used is a quantitative research approach. Data collection techniques use questionnaires, observation, documentation. Data is measured using a Linkert scale with a range of 5 options. Statistical analysis uses multiple linear regression analysis techniques. The respondents of this research are students of the Communication Science Study Program, Even Semester, Academic Year 2022-2023. The research results show that there is a relationship between the Solopos.com media agenda and the public agenda regarding the electability of presidential candidates. The political situation leading up to the 2024 election is an important moment for the Solopos.com media which is directly or indirectly participating in branding candidates Anies Bawesdan and Ganjar Pranowo as presidential candidates.